Familial hypercholesterolaemia with early-onset coronary artery disease and recurrent in-stent restenosis associated with the LDLR gene c.428G>A mutation: a case report - Chengpeng Zhang; Hui Li; Wei Zhang; Jian Huang; Jing Zhu (Frontiers in Cardiovascular Medicine)
BackgroundFamilial hypercholesterolaemia (FH) is characterised by significantly elevated low-density lipoprotein cholesterol (LDL-C) levels and early-onset coronary artery disease. Additionally, clopidogrel resistance is observed in approximately 30%–50% of individuals globally. Among FH patients with early-onset coronary artery disease, inadequate LDL-C management and suboptimal antiplatelet therapy after stent implantation are key factors contributing to recurrent in-stent restenosis (ISR).Case presentationA 65-year-old male with a history of coronary artery disease (CAD), hyperlipidemia, and prior angioplasty presented to our institution with exacerbation of angina symptoms. The patient's CAD was initially diagnosed at age 52 (early-onset), with subsequent coronary angiography performed at Lianshui County Hospital. Coronary angiography confirmed coronary artery disease, prompting percutaneous coronary intervention (PCI) with stent placement: one in the right coronary artery and another in the left circumflex artery. Despite receiving standard antiplatelet (aspirin enteric-coated tablets 100 mg, clopidogrel 75 mg) and lipid-lowering therapy (pitavastatin calcium 2 mg), his LDL-C levels remained poorly controlled, and chest pain recurred. At the age of 62 and 65, he developed ISR with additional coronary artery lesions, necessitating balloon angioplasty. FH gene sequencing and clopidogrel resistance testing found he have a heterozygous LDL receptor (LDLR) gene mutation (c.428G>A, p.Cys143Tyr) and a clopidogrel genotype of CYP2C19 *1/*2. Based on these findings, his antiplatelet and lipid-lowering therapies were adjusted (aspirin 100 mg, clopidogrel 150 mg, rosuvastatin 10 mg, ezetimibe 10 mg and alirocumab 150 mg biweekly). Follow-up revealed that his LDL-C levels reached target values, and he remained asymptomatic. One year later, coronary angiography showed no disease progression, and the patient experienced no recurrence of chest pain. This case highlights the efficacy of precision treatment.ConclusionsFor FH patients with early-onset CAD who are intolerant to ticagrelor, early implementation of FH genetic sequencing and clopidogrel genotyping is critical for personalised treatment.